Selective abiotic and biotic stressors influence the acdS gene abundance in the rhizospheric soil of pineapple plants in Lampung, Indonesia - Jaya, Dori Kusuma; Giyanto, Giyanto; Nurhidayat, Novik; Antonius, Sarjiya (UNIVERSITY OF LAMPUNG, 2024)
Indonesia has faced extensive poor soil quality and health for years.Anthropogenic, climatic, and plant pathogenic activities are the major contributing factors that degrade the soil's essential life-supporting system, such as the functional gene pool. One such gene is the rhizobacterial acdS, which codes for synthesizing the ACC (1-aminocyclopropane-1-carboxylate) deaminase that cleaves ACC as an ethylene hormone precursor in the stressed plant growing under stressful conditions. This study aims to investigate the abundance of the acdS gene in different abiotic and biotic stressors of the rhizospheric soil of pineapple plantation area that has been exposed incidentally to herbicides, flooding, and pathogenic Phytophthora spp infections. Soil samples were collected by using simple randomized sampling. A quantitative real-time polymerase chain reaction (qPCR)-based method was applied to assess the gene abundance. This study reveals that the abundance of acdS in the rhizospheric soil of herbicide-treated and Phytophthora-infected symptomatic plants is relatively lower than that of non-treated ones. The highest abundance was found in the Phytophthora-infected soil of asymptomatic plants. However, there was no significant difference in abundance between the fflooded rhizospheric soil TO rhizospheric soil of flooded-exposed plants and the non-exposed ones. Hopefully, this data will help us better understand proper land-use management practices for pineapple plants.